Characterization of Three Indica Rice Multiparent Advanced Generation Intercross (MAGIC) Populations for Quantitative Trait Loci Identification - Meng, Lijun; Guo, Longbiao; Ponce, Kimberly; Zhao, Xiangqian; Ye, Guoyou (Wiley, 2016)
Three new rice (Oryza sativaL.) multiparent advanced generation intercross (MAGIC) populations were developed using eight eliteindicarice varieties from different breeding programs. These three populations were two recombinant inbred line (RIL) populations derived from two 4‐way crosses, DC1 and DC2, and one RIL population derived from an 8‐way cross. These populations were genotyped using an Illumina Infinium rice 6K SNP chip. The potential of the three MAGIC populations in identifying marker–trait associations was demonstrated using the plant height (PH) and heading date (HD) measured in 2014. A population of 248 IRRI breeding lines and a population of 323 Chinese breeding lines were also included to compare genetic diversity and linkage disequilibrium (LD) pattern. Our study discovered that (i) the 8‐way population had a higher gene diversity than the DC1, DC2, and IRRI populations; (ii) all three MAGIC populations showed no clear population structure; (iii) LD decayed tor2< 0.2 at about 2.5, 2.5, 1.25, 1.75, and 4.0 Mb for the DC1, DC2, 8‐way, IRRI, and Chinese populations, respectively; and (iv) the 8‐way population was more powerful than the DC1, DC2, and IRRI populations on QTL identification. The association analysis identified two and three QTL for PH and HD, respectively. Four of the five QTL had peak markers close to known genes. A novel QTL for PH was identified on chromosome 12 using the 8‐way population. Therefore, our study suggests that the three new MAGIC populations are valuable resources for QTL identification.